Pengembangan bahan ajar konsep pengantar bioteknologi untuk peserta didik fase E berbentuk e-handout - Khalida, Noor; Noorhidayati, Noorhidayati; Amintarti, Sri (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
21st century learning demands creativity and innovation in the idea of digitizing teaching materials to facilitate students’ 6C competencies. The teaching material was chosen is E-handout. This study aims to describe the suitability, feasibility and readability of the results of the Development of Teaching Materials for Biotechnology Introduction Concepts for Phase E Students in the form of E-handout. This research uses the 4D model of Thiagarajan et al. (1974). The data collection technique uses validation instruments for suitability, feasibility and readability of students. The suitability and feasibility test subjects consisted of 3 validators. The readability test subjects consisted of 9 students of class XI-4 at SMAN 4 Banjarmasin T.A. 2023/2024. The results of research on the Development of Teaching Materials for Biotechnology Introduction Concepts for Phase E Students in the form of E-Handouts obtained: (1) The average suitability score of 4.62 which is classified as